2018
DOI: 10.1093/jxb/ery261
|View full text |Cite
|
Sign up to set email alerts
|

Early mannitol-triggered changes in the Arabidopsis leaf (phospho)proteome reveal growth regulators

Abstract: We captured early changes in the Arabidopsis thaliana growing leaf proteome and phosphoproteome upon mild mannitol stress and pinpointed novel regulators of shoot growth.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 77 publications
1
30
0
Order By: Relevance
“…Unfortunately, the latter studies lack organ-level resolution necessary to draw conclusions about the timing at which these phosphoproteome changes occur in the shoot. Specifically in shoots, transcriptomics and proteomics analyses found notable osmotic stress-induced changes within 30~60 minutes following osmotic stress (Skirycz et al, 2011a;Nikonorova et al, 2018). Overall, these studies situate the short-term stress response in aerial plant tissues of Arabidopsis around 10~60 minutes upon stress sensing by the roots.…”
Section: Within the First Hour Leaves Close Stomata And Initiate Gromentioning
confidence: 68%
See 2 more Smart Citations
“…Unfortunately, the latter studies lack organ-level resolution necessary to draw conclusions about the timing at which these phosphoproteome changes occur in the shoot. Specifically in shoots, transcriptomics and proteomics analyses found notable osmotic stress-induced changes within 30~60 minutes following osmotic stress (Skirycz et al, 2011a;Nikonorova et al, 2018). Overall, these studies situate the short-term stress response in aerial plant tissues of Arabidopsis around 10~60 minutes upon stress sensing by the roots.…”
Section: Within the First Hour Leaves Close Stomata And Initiate Gromentioning
confidence: 68%
“…In young Arabidopsis leaves, 57 transcripts respond within 1.5 h of stress, or even earlier (Skirycz et al, 2011a;Dubois et al, 2015;Nikonorova et al, 2018). The majority of these genes is involved in ethylene response and, consistently, osmotic stress was shown to trigger an increase in ACC levels in young seedlings after 1 h (Fig.…”
Section: Within the First Hour Leaves Close Stomata And Initiate Gromentioning
confidence: 84%
See 1 more Smart Citation
“…Protein phosphorylation has been reported as one of the early posttranslational responses to osmotic stress (Nikonorova et al, 2018), and QSK1 has multiple phosphorylation sites and is phosphorylated in response to abiotic stress (Niittylä et al, 2007;Chang et al, 2012). Using phosphomutants of QSK1, we showed that the phosphorylation status of QSK1 is important for subcellular localization with the QSK1-S621D,S626D-GFP phosphomimic mutant partially associating with plasmodesmata even in control conditions, while the QSK1-S621A,S626A-GFP phosphodead mutant was significantly affected in its capacity to localize to plasmodesmata after mannitol treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A reduced group of these SnRK3 sequences could be considered founder as were close in the sequence tree to microalgae SnRK3/CKIN3 (Figure 1). Interestingly, between the plant sequences included in this group are Arabidopsis SnRK3.11 or SOS2, a salt stress responsive kinase within the SOS pathway [33], osmostress-sensitive SnRK3.13 [35] and P. pinaster PpiSnRK3.3 and PpiSnRK3.4. This closeness points at once to the ancient (microalgae) origin of this pathway and by analogy to the possible involvement of both microalgae and P. pinaster PpiSnRK3.3 and PpiSnRK3.4 into salt and/or osmotic stress responses.…”
Section: Discussionmentioning
confidence: 99%